Epidemiologic and Microbiologic Characteristics of Occult Bacteremia Among Febrile Children in Southern Israel, Before and After Initiation of the Routine Antipneumococcal Immunization (2005-2012) - Haya Ribitzky-Eisner; Yitamar Minuhin; David Greenberg; Ninel Greenberg; Gabriel Chodick; Mihai Craiu; Eugene Leibovitz (Elsevier, 2016)
Little is known about the incidence and dynamics of occult bacteremia (OB) among infants/young children following the introduction of pneumococcal conjugate vaccines (PCVs) into the national immunization program in Israel in 2009-2010. The aim of this study was to characterize the epidemiologic and microbiologic picture of OB among febrile infants/children aged 3-36 months in southern Israel, before and after PCVs introduction. Methods: Retrospective study enrolling all infants/young children attending the emergency room of a tertiary medical center in southern Israel with fever without source, discharged, and reported with a positive blood culture. Results: Of 453 true bacteremias, 89 (19.6%) were defined as OB. OB rate was 0.22%; a significant decrease was recorded in OB rates, with the highest rate during 2005 (0.34%) and the lowest during 2011 (0.15%). OB cases decreased in post-PCV (2010-2012) versus prevaccination period (2005-2009) from 66/22,256 cases (0.3%) to 23/13,213 cases (0.17%; p = 0.03). Most frequent single OB pathogens were Streptococcus pneumoniae, Streptococcus viridans spp., and Kingella kingae (39.3%, 10.1%, and 9.0%, respectively); Enterobacteriaceae spp. were isolated in 10 cases (11.2%). No changes were recorded in S. pneumoniae-OB cases; K. kingae-OB decreased significantly (p = 0.047). None of the S. pneumoniae serotypes isolated during 2011-2012 belonged to 13-valent PCV (PCV13). An increase in non PCV13 serotypes was recorded during 2011-2012 (3/3, 100% vs. 7/32, 21.9%, p = 0.01). Conclusion: OB rates decreased significantly following the introduction of PCVs. S. pneumoniae was the most frequent isolated pathogen in OB, but in lower percentages compared with the medical literature. No PCV13 serotypes were detected as a cause of OB during 2011-2012.